2022
DOI: 10.3389/fimmu.2022.832230
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT Blockade Exerts Synergistic Effects on Microwave Ablation Against Cancer

Abstract: BackgroundCombination immunotherapy based on immune checkpoint inhibitors (ICIs) has shown great success in the treatment of many types of cancers and has become the mainstream in the comprehensive treatment of cancers. Ablation in combination with immunotherapy has achieved tremendous efficacy in some preclinical and clinical studies. To date, our team proved that ablation in combination with ICIs was a promising antitumor therapeutic strategy for the liver metastasis of colorectal cancer (CRC). Moreover, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 61 publications
(71 reference statements)
4
27
0
Order By: Relevance
“…For example, it has been suggested that in the tumor model established by 4T1 breast cancer cells, the MWA can activate the T-cell immune response, and the combination therapy based on MWA can significantly induce the Th1-type anti-tumor response [10]. Moreover, we have previously confirmed that MWA combined with TIGIT blockade exerts synergistic effects against cancer in contrast to MWA or TIGIT blockade alone [12].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…For example, it has been suggested that in the tumor model established by 4T1 breast cancer cells, the MWA can activate the T-cell immune response, and the combination therapy based on MWA can significantly induce the Th1-type anti-tumor response [10]. Moreover, we have previously confirmed that MWA combined with TIGIT blockade exerts synergistic effects against cancer in contrast to MWA or TIGIT blockade alone [12].…”
Section: Introductionsupporting
confidence: 68%
“…The MC38 cells (mouse colon cancer cell line) in the present study have been used in our previous report [12]. MC38 cells were maintained in DMEM supplemented with 10% (v/v) fetal bovine serum (FBS, Gibco, Thermo Fisher Scientific, USA), 100 U/mL penicillin, and 100 µg/ mL streptomycin.…”
Section: Cell Line and Micementioning
confidence: 99%
See 1 more Smart Citation
“…TA is considered a safe treatment for primary lung cancer ( 7 , 20 , 21 ). As an alternative therapy to surgical resection, TA causes irreversible damage to tumor cells using thermal energy ( 14 , 31 , 32 ). While previous studies have shown that TA is beneficial for stage I NSCLC patients ( 7 , 18 , 33 ), however, there is minimal data on the use of TA in stage II-III NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell RNA-seq (scRNA-seq) data analysis and different expression gene analysis Our scRNA-seq data were processed by the methods as we previously described. 41 Briefly, cells with less than 6000 unique molecular identifiers (UMIs) count, 10% mitochondrial gene count, and 40% ribosomal gene count were used for integration of multiple scRNA-seq, dimension reduction and unsupervised clustering. All visualization plots were applied by Seurat function and ggplot2 package.…”
Section: Tcr Repertoire Analysismentioning
confidence: 99%